2022
DOI: 10.3390/ijms23158513
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Treating Early and Advanced Stage Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of preventable blindness in the working-age population. The disease progresses slowly, and we can roughly differentiate two stages: early-stage (ESDR), in which there are mild retinal lesions and visual acuity is generally preserved, and advanced-stage (ASDR), in which the structural lesions are significant and visual acuity is compromised. At present, there are no specific treatments for ESDR and the current recommended action is to optimize metabolic control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 108 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…GLX7013114 (NOX4 specific inhibitor) protected retinal OS and neuroinflammation damage, but had no effect on neural dysfunction (22). These findings suggested that NOX (1,2,4) are important players in the pathophysiology of retinal disease, whose pathophysiology involves excitotoxicity and OS that lead to alterations in retinal neurons and glia.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…GLX7013114 (NOX4 specific inhibitor) protected retinal OS and neuroinflammation damage, but had no effect on neural dysfunction (22). These findings suggested that NOX (1,2,4) are important players in the pathophysiology of retinal disease, whose pathophysiology involves excitotoxicity and OS that lead to alterations in retinal neurons and glia.…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical hallmarks include the breakdown of the blood-retinal barrier (BRB), vascular microaneurysms, endothelial cell proliferation, and neovascularization (late stage). Mild non proliferative DR (NPDR; early stage) precedes PDR and is characterized by retinal neurodegeneration, glial activation,vasculopathy and leaky vessels (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations